Description of 90 inbred lines of castor plant (Ricinus communis L.) - Baldanzi, Marco; Myczkowski, Mirina Luiza [UNESP]; Salvini, Mariangela; Macchia, Mario (Springer, 2015)
The research describes the field comparison of 90 inbred lines of castor plant derived from both selected and wild germplasm. It was carried out in central-western Italy. An important aim of this work was to describe each inbred line based on 19 morphological traits concerning stem, leaves, racemes and capsules and then to suggest a list of descriptors to International Union for the Protection of New Varieties of Plants as to conduct the Distinctness, Uniformity and Stability test also on the castor plant. The plants in the field were grown at wide distances to avoid competition and enable observation of the growth habit, particularly the specific capacity of branching. An additional characterization of the inbred lines was obtained measuring 7 quantitative traits related to main stem and first raceme; the number of racemes per plant was used to quantify the plant branching. The results allowed distinguishing almost all the genotypes using only the morphological traits. Nectaries at the node, emergences on the stem and petioles, colour of nectaries on petiole resulted important plant descriptors. The two pairs of inbred lines (Tor87#9 vs. Tor87#83 and Pod87#255Hy2 vs. Rot95#55-23) were distinguished thanks to the quantitative traits. Based on the morphological traits, two UPGMA dendrograms, one for the dwarf and one for the normal genotypes, were characterized and the resulting clusters better explained the relationships among the various inbred lines. Six genotypes (Pod87#389, Tor87#81A, Tor87#220B, Tor87#287, Tor87#287Hy, and Liba21) resulted unable to flower in the field; in these inbred lines the induction to flower is particularly influenced by the environmental growth conditions. Regarding the branching ability, the strong apical dominance of two inbred lines (Pod94#31-2 and Pod93#211) obtained from previous breeding programs was confirmed and it was possible to detect other interesting genotypes (Pod87#287A, Pod87#287B, Tor86#67). The several inbred lines described herein showed a wide range of phenotypes that might be useful in various fields of research.
Keywords: DUS test; Metric traits; Plant descriptors; Plant morphology; UPGMA; UPOV